Intelligent Image Capturing Alarm System Using Raspberry Pi - K.A.M. Annuar; N.A. Ab Hadi; S.K. Subramaniam; M. F. Mohd Ab Halim; M.B. N. Shah; A.F. Kadmin; M.S. Amri; A. Abdul Salam (Universitas Ahmad Dahlan, 2017)
Home surveillance system assumes an essential part in this present day living style to help recognizing illegal activities. In this proposed paper, an intelligent image capturing alarm system to protect locker was developed. Raspberry Pi 2 is used as the main controller (server). At the point when any conceivable intrusion is identified, a webcam installed to Raspberry Pi 2 will capture the picture of the intruder. In the meantime, the spotlight or light of the house which represented by an LED will be turned